Nilai Pendidikan Karakter dan Kearifan Lokal dalam Cerita Rakyat Banyumas serta Implementasinya terhadap Pembelajaran Bahasa Indonesia - Nurlaili, Fadilla Intan; Sukirno (Proceedings Series on Social Sciences & Humanities, 2024)
This research aims to examine the values of character education and local wisdom contained in Banyumas folklore and its implementation in Indonesian language teaching in high schools. Folktales such as "Babad Ajibarang," "Babad Sokaraja," and "Bendera Panji Wulung" were analyzed using a descriptive qualitative method with an inferential content analysis approach. The results show that these stories contain character values such as courage, perseverance, justice, wisdom, loyalty, and honesty. These values are not only relevant for the character formation of students but also enrich the learning materials by introducing local culture and traditions. The implementation of folktales in Indonesian language learning can be done through activities such as analysis and drama performances, which help students understand and apply character values in their daily lives. This research provides an important contribution to the development of teaching materials based on folktales and guides teachers in integrating character education and local wisdom values into the learning process.